Oxygen-mediated acceleration of chloride capture and migration by copper oxide in PVC-based cable pyrolysis - Zou, Yanyan (2024)
The incineration of a large number of old cables leads to the problem of green recycling and causes a lot of environmental problems. This paper investigates the effect of copper oxide (CuO) capture of chlorine (Cl) in the pyrolysis recycling of polyvinyl chloride (PVC)-based waste cable outer sheath, focusing on the redistribution of the contaminant Cl components under the action of oxygen (O2). Analytical methods such as ion chromatography and diffraction of X-rays are employed to measure and quantify the dynamic changes of the Cl-containing three-phase products during the pyrolysis process. The results indicate that, compared to copper (Cu), the oxidized state of CuO and O2-rich conditions can enhance the capture of Cl. With increasing O2 supply, 1.71–6.33 mass% of gas-phase Cl and 14.52–29.96 mass% of liquid-phase Cl convert into 16.23–36.29 mass% of solid-phase Cl. CuO reacts directly with the PVC component of the outer sheath in a solid–solid reaction, significantly reducing the generation of polluting Cl-containing aromatic compounds in the liquid-phase tar and synergistically facilitating CaCO3 components to intimately contact with the pyrolysis gas to capture HCl. The originally stable CuCl2 crystals are oxidized again to enter into cyclic adsorption in the form of CuO under O2-rich conditions. Cl is more fixed in the residue and primarily exists in the form of stable and safe CuCl2 and CaCl2 metallic compounds. This study has clearly elucidated the efficient in situ green solidification mechanism of Cl during the treatment of cable waste with CuO in the presence of O2, providing new recommendations for cable sheath formulations and solid waste management.